309 Genetic testing in childhood: ethics in practice. (17th August 2022) - Hart, Rachel; Clarke, Angus; Hall, Alison
Abstract : Aims: The British Society for Genetic Medicine established a working group to review its guidance on the practical ethics of genetic testing in childhood. The review was timely, given the challenges presented by mainstreaming genomics and with the progress in laboratory technology and bioinformatics. Methods: A multi-disciplinary working group of geneticists, paediatricians, social scientists, philosophers and lawyers collaborated to prepare the report. A workshop was held in February 2020 to agree a draft structure and the group then worked iteratively to finalise the report. Results: The new guidance describes relevant ethical and legal frameworks and provides a clinical section of worked examples highlighting specific ethical issues. These include the importance of balancing the benefits and risks of genetic testing in childhood, and potential challenges of generating variants of uncertain significance and unexpected findings. Expansion of genetic testing to broader panels, whole genome sequencing and whole exome sequencing is proving challenging. Genetics specialists will need to support colleagues during the process of 'mainstreaming'. Proposals for the genomic screening of healthy children need to be weighed carefully before being introduced. While it may be proper to use genetic test results on a child to benefit other family members, undertaking a test with that as the primary goal of testing would usually be inappropriate. Conclusion: This document brings together current thinking on the ethical issues that are potentially generated by genetic and genomic testing in children. By illustrating these issues through worked examples to highlight particular ethical challenges, it facilitates any users of genomic testing in children to navigate some of the potential issues that may arise. This report builds on broader guidance from the British Society for Genetic Medicine publication dealing with ethical issues relating to consent and confidentiality. Rather than providing guidance on detailed clinical management (although links are provided to relevant publications), both these publications support best practice and support the need for good understanding of genomic testing and interpretation of results in order to provide informed consent to families about their testing.